2016
DOI: 10.1162/jocn_a_00906
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Emotional States on Cognitive Control Circuitry and Function

Abstract: Typically in the laboratory, cognitive and emotional processes are studied separately or as a stream of fleeting emotional stimuli embedded within a cognitive task. Yet in life, thoughts and actions often occur in more lasting emotional states of arousal. The current study examines the impact of emotions on actions using a novel behavioral paradigm and functional neuroimaging to assess cognitive control under sustained states of threat (anticipation of an aversive noise) and excitement (anticipation of winning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 94 publications
5
44
0
6
Order By: Relevance
“…Cohen et al (2016) showed that sustained, but not transient, positive and unpleasant emotional states are associated with changes in performance and altered neural activation and connectivity in healthy adults. They did so by demonstrating that the brief presentation of emotional cues less efficiently modulates cognitive control capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohen et al (2016) showed that sustained, but not transient, positive and unpleasant emotional states are associated with changes in performance and altered neural activation and connectivity in healthy adults. They did so by demonstrating that the brief presentation of emotional cues less efficiently modulates cognitive control capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the studies described above showed concomitant competition for representation in WM because the emotional stimulus was presented in a randomized manner during the experimental session. However, emotion-cognition interaction has also been investigated across longer timescales in studies that induced a sustained emotional state (Bradley et al , 1996; Smith et al , 2005; Pereira et al , 2006; Brouwer et al , 2013; Ben-Haim et al , 2014), and this approach may be related to enhanced modulation of cognitive control by emotional stimuli (Cohen et al , 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited from Los Angeles and New York City as part of a larger study. Participants were 21.6% African American, 14.8% Asian, 36.9% Caucasian, 22.7% Hispanic, and 4.0% “other.” Participants were randomly assigned to one of two conditions—“Alone” (97 completed the go/no‐go task as reported in Cohen, Dellarco, et al, ) or “Peer” (79 completed the go/no‐go task under the impression that a same‐aged, same‐gender peer was watching and evaluating their performance). Assignment into the peer versus alone group was counterbalanced across subjects and sites.…”
Section: Methodsmentioning
confidence: 99%
“…All participants completed the Cognitive Control Under Emotion (CCUE) task (Cohen, Dellarco, et al, , Supplementary Figure S1) programmed using E‐Prime 2.0. In the task, participants were presented with smiling, fearful, and neutral face cues while under sustained anticipation of a negative event (an aversive sound), positive event (winning up to $100), or neutral event (no risk of a positive or negative event).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation